Pengaruh Gaya Kepemimpinan dan Kepuasan Kerja Terhadap Kinerja Karyawan di Perusahaan PT. Boiler Total Solution - Endang Risbaya; Yuli; Kanta; Karnawi Kamar (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to determine: (1) The partial effect of leadership style on employee performance, (2) The partial effect of job satisfaction on employee performance, and (3) The simultaneous effect of leadership style and job satisfaction on employee performance. This study uses a quantitative approach with an associative research type. The population in this study were all employees of PT. Boiler Total Solution. Sampling used a probability sampling technique with a simple random sampling category. Data were collected through questionnaires and analyzed with the help of SPSS version 18.00. Data analysis included validity and reliability tests, multiple linear regression, t-tests, and F-tests. The results of the study indicate that leadership style and job satisfaction have a positive and significant effect on employee performance both partially and simultaneously.